The Unstressed Vowel Reduction of Galician - Alba Aguete Cajiao (Languages)
This study investigates the unstressed reduction process of Galician. In particular, we wondered about: (1) the specific mechanisms involved, (2) whether there are different degrees of reduction, depending on the word-stress position, or whether reduction applies categorically to all unstressed vowels, (3) whether it depends on the duration, and (4) whether it is a mechanical process. In order to answer those questions, an experimental acoustic study with semi-spontaneous speech from six young Galician-native women was conducted. The results were analyzed by applying individual linear mixed-effects models for each vowel. The results show that two different mechanisms are involved in the reduction process, namely raising and centralization, and conclude that, in Galician, this process does not depend on the duration of the segment, and, thus, it is controlled by the grammar of the language.